2018
DOI: 10.1111/corg.12237
|View full text |Cite
|
Sign up to set email alerts
|

The effect of estate tax change on the controlling shareholding structure and corporate value of family firms

Abstract: Manuscript type Empirical Research question/issue Estate tax planning has always been a primary concern of large shareholders when arranging the controlling shareholding structure of family firms. This paper provides evidence on the effect of a drastic change in estate tax on the shareholding structure of family‐controlled firms in Taiwan, as well as the impact of these changes on the firms' corporate value. We examine a 2008 policy change in Taiwan that substantially reduced the estate tax from a maximum rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…We conduct a second robustness test to account for the sensitivity of observed outcomes to different family firm definitions (Sacristán-Navarro et al, 2011). In this test, we use the definition of family firms provided by Yeh and Liao (2019). A firm is a family firm if one of the following three criteria is met: (a) the founding family controls at least 20% of the shares of the firm, (b) the founding family controls at least 50% of the board of director seats, (c) the chair of the board of directors and the general manager of the firm are from the same family.…”
Section: Robustness Testsmentioning
confidence: 99%
“…We conduct a second robustness test to account for the sensitivity of observed outcomes to different family firm definitions (Sacristán-Navarro et al, 2011). In this test, we use the definition of family firms provided by Yeh and Liao (2019). A firm is a family firm if one of the following three criteria is met: (a) the founding family controls at least 20% of the shares of the firm, (b) the founding family controls at least 50% of the board of director seats, (c) the chair of the board of directors and the general manager of the firm are from the same family.…”
Section: Robustness Testsmentioning
confidence: 99%
“…Given the context dependence of this firm behaviour, it requires further research (Lanis and Richardson, 2011), and more specifically, the relationship between tax avoidance and family firms (Steijvers and Niskanen, 2014; Sánchez-Marín et al. , 2016; Yeh and Liao, 2019; Khelil and Khlif, 2022). Some of the literature on family firms' tax aggressiveness has focused on either large or public companies, selected exclusively based on family ownership.…”
Section: Introductionmentioning
confidence: 99%
“…The international scope of corporate governance research is indicated by the diverse set of governance environments studied in recent CGIR articles that include Australia, Canada, China, Germany, India, Indonesia, Iran, Italy, Japan, Korea, Russia, Spain, Sweden, Taiwan, the United Kingdom, the United States, and Vietnam, as well as multicountry studies (e.g., Deloof, Du, & Vanacker, 2020; Desender, LópezPuertas‐Lamy, Pattitoni, & Petracci, 2020; García‐Sánchez & García‐Meca, 2018; Lazzarini & Musacchio, 2018; Qian, Cao, & Cao, 2018; Tribó, 2019; Zhou & Guillén, 2019). Corporate governance research is by no means restricted to the average publicly held corporation but also deals with the unique challenges associated with specific types of firms like, for instance, audit firms (La Rosa, Caserio, & Bernini, 2019), banks (Sheedy & Griffin, 2018), business groups (Shin, Hyun, Oh, & Yang, 2018), closely held firms (Russino, Picone, & Dagnino, 2019), declining firms (Abebe & Tangpong, 2018), entrepreneurial ventures (Pérez‐Calero, Larrañeta, & Wright, 2019), family firms (Yeh & Liao, 2019), foundations (Thomsen, Poulsen, Børsting, & Kuhn, 2018), institutional investors (Semenova & Hassel, 2019), intergovernmental organizations (Federo & Saz‐Carranza, 2018), initial public offerings (IPOs) (González, Guzmán, Tellez‐Falla, & Trujillo, 2019), as well as state‐owned enterprises (Apriliyanti & Randøy, 2019). This research intensity demonstrates the spread of corporate governance studies in multiple disciplines but also leads to higher levels of fragmentation of the field.…”
Section: Introductionmentioning
confidence: 99%
“…. Corporate governance research is by no means restricted to the average publicly held corporation but also deals with the unique challenges associated with specific types of firms like, for instance, audit firms (La Rosa, Caserio, & Bernini, 2019), banks (Sheedy & Griffin, 2018), business groups (Shin, Hyun, Oh, & Yang, 2018), closely held firms (Russino, Picone, & Dagnino, 2019), declining firms (Abebe & Tangpong, 2018), entrepreneurial ventures (Pérez-Calero, Larrañeta, & Wright, 2019), family firms (Yeh & Liao, 2019), foundations (Thomsen, Poulsen, Børsting, & Kuhn, 2018), institutional investors (Semenova & Hassel, 2019), intergovernmental organizations (Federo & Saz-Carranza, 2018), initial public offerings (IPOs) (González, Guzmán, Tellez-Falla, & Trujillo, 2019), as well as state-owned enterprises (Apriliyanti & Randøy, 2019). This research intensity demonstrates the spread of corporate governance studies in multiple disciplines but also leads to higher levels of fragmentation of the field.…”
mentioning
confidence: 99%